2023
DOI: 10.1128/spectrum.00286-23
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Aeromonas Infection: a Common Enteric Bacterial Infection with a Novel Infection Pattern Detected in an Australian Population with Gastroenteritis

Abstract: Aeromonas species are emerging human enteric pathogens. However, these species are currently not routinely detected in many diagnostic laboratories, and no studies have reported the detection of Aeromonas enteric infection using molecular methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Whereas Aeromonas was identified in <1 % of the children in four African sites, it was markedly more prevalent in the Karachi (Pakistan) and Mirzapur (Bangladesh) GEMS sites, identified as a significant pathogen in 22.2 % of MSD cases [ 9 ]. Aeromonas has also been identified as the second most commonly isolated candidate enteric bacterial pathogen in children below 18 months with gastroenteritis in Australia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Aeromonas was identified in <1 % of the children in four African sites, it was markedly more prevalent in the Karachi (Pakistan) and Mirzapur (Bangladesh) GEMS sites, identified as a significant pathogen in 22.2 % of MSD cases [ 9 ]. Aeromonas has also been identified as the second most commonly isolated candidate enteric bacterial pathogen in children below 18 months with gastroenteritis in Australia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Australian study revealed that Aeromonas spp. exhibited a distinct infection pattern in human gastroenteritis compared to other enteric bacterial pathogens [ 6 ]. Across all age groups, three infection peaks occurred in young children under four, young adults aged 20–29, and adults over 50.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, infection rates of Campylobacter spp., Salmonella spp., Shigella spp./enteroinvasive Escherichia coli and Yersinia spp. in the same age group were 320, 294, 19 and 42 per 10 000 samples, respectively [ 6 ]. Additionally, patients with inflammatory bowel disease (IBD) are more likely to be infected with Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%